A scoping review of mHealth monitoring of pediatric bronchial asthma before and during COVID-19 pandemic. (September 2022) - Dauletbaev, Nurlan; Oftring, Zoe S.; Akik, Wided; Michaelis-Braun, Lukas; Korel, Julia; Lands, Larry C.; Waldmann, Susanne; Müller, Beate S.; Dreher, Michael; Rohde, Gernot; Vogelmeier, Claus F.; Kuhn, Sebastian
Abstract: Mobile (m) Health technology is well-suited for Remote Patient Monitoring (RPM) in a patient's habitual environment. In recent years there have been fast-paced developments in mHealth-enabled pediatric RPM, especially during the COVID-19 pandemic, necessitating evidence synthesis. To this end, we conducted a scoping review of clinical trials that had utilized mHealth-enabled RPM of pediatric asthma. MEDLINE, Embase and Web of Science were searched from September 1, 2016 through August 31, 2021. Our scoping review identified 25 publications that utilized synchronous and asynchronous mHealth-enabled RPM in pediatric asthma, either involving mobile applications or via individual devices. The last three years has seen the development of evidence-based, multidisciplinary, and participatory mHealth interventions. The quality of the studies has been improving, such that 40% of included study reports were randomized controlled trials. In conclusion, there exists high-quality evidence on mHealth-enabled RPM in pediatric asthma, warranting future systematic reviews and/or meta-analyses of the benefits of such RPM.